Unemployment duration tables - Bieszk-Stolorz, Beata; Markowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The purpose of the article is to construct the registered unemployment duration table. The table is a non-parametric model (also called a tabular model) showing the duration of a given phenomenon. In demography it is most often used as a life (or mortality) table. We will construct the cohort tables on the basis of individual data provided by the Poviat Labour Office in Szczecin. The cohort will consist of unemployed individuals registered in 2012 and observed by the end of 2013. The event regarded as the one ending the unemployment spell will be the moment of an individual’s de-registration from the PLO due to finding employment. The remaining data have been considered censored. One of the elements of the table is hazard intensity. We will compare the intensities of unemployment exits in the cohort subgroups.